Letras y Limpias : Decolonial Medicine and Holistic Healing in Mexican American Literature - Ellis, Amanda, 1981- (Book collections on Project MUSE., 2021)
"In Letras y Limpias, Amanda V. Ellis analyzes depictions of the figure of the curandera, or folk healer, in foundational texts of Mexican American literature. It is the first full-length study to provide a literary history of representations that depict folk healing. In doing so, it argues that curanderismo, and more specifically the figure of the curandera, throughout literature is a figurative watermark that personifies both the continuity and discontinuity among three disparate historical periods of the Mexican American literary archive (pre-Chicano Movement writing, Chicano Nationalist Movement writing, and Post-Chicano Nationalist Movement writing). Ellis argues that the persistence of this figure in Mexican American literary tradition is an act of decolonial discursive resistance that poses a call for holistic healing"--